Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Berdasarkan Standar BUMN Pada PT. Semen Tonasa (Persero) Periode 2016-2021 - Risdayanti Idris; Romansyah Sahabuddin; Nurman; Hety Budiyanti; Siti Hasbiah (CV. Lafadz Jaya, 2023)
This study aims to determine the financial performance of PT. Semen Tonasa based on financial ratios using SOE Standards for the 2016-2020 period. This research is a quantitative descriptive study. The population in this research is the financial statements of PT. Semen Tonasa for the 2016-2020 period. The sample in this study is the statement of financial position and profit and loss of PT. Semen Tonasa Period 2016-2020. Data collection techniques in this study are using interviews and documentation techniques. The results of the research that has been done show that the financial ratio analysis of PT. Semen Tonasa (Persero) for the 2016-2020 period based on the Decree of the Minister of BUMN No: KEP-100/MBU/2002 it can be concluded that the financial performance in 2016-2020 earned the AA category with the HEALTHY predicate, except in 2017 it received the A category with the HEALTHY predicate, with a total score of 64.5 in 2016, 53 in 2017. 60.5 in 2018 and 59.5 in 2019-2020 years.